Aure musicali in Dante - CAPPUCCIO , Chiara (Cuadernos de Filología Italiana, 2010)
In this article the author proposes a philological and musicological analysis of the 22-30 vv. from III chant of the Inferno, slightly different from traditional interpretations. Starting from the old comment by Jacomo della Lana, and with a new interpretation of the sintagma sanza tempo (Inf. III, 30), we individuate, in the famous terzine that constitute the first description of hell, two synaesthesiae until now not yet discovered – figure that performs a paradigmatic function in the narrative genesis of the Commedia – upon which a rethoric construction of the analysed verses is built. This new reading allows us to establish an intertextual parallelism between the entrance to hell and the entrance to terrestrial paradise (Inf. XXVII, 7-21). The use of a semantic set produces a rhetoric, diegetic and ideological correspondence between the two moments privileged in Dante’s work which has not been highlighted until now in the critic.
Keywords: Inferno; Synaesthesia; Music; Jacomo della Lana; Convivio